Tidal Energy-based Optimal Microgrid Planning with the Presence of Electric Vehicles - et. al., Farshad Heidarpour, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The development of clean and renewable energy has led to modern planning and operation of power systems. Tidal energy is seen as one of the newest energy resources used to generate electrical power. In power generation systems, the tides in a river direct seawater flow towards hydraulic turbines and generate electric power through conventional induction or doubly-fed induction generators (DFIG). These electric power generation systems can be utilized in the form of coastal microgrids including electric charges, storage systems, and plug-in electric vehicles (PEVs). Although the velocity and direction of water flow in tidal energy systems are predictable, its variability hinders its utilization in the form of coastal microgrids. On the other hand, since electric vehicle parking lots can serve as part of the charging or generation system in the coastal microgrids, and also considering the fact that the random behavior of drivers makes power consumption or generation of parking lots random in nature, it will be highly important to optimally design these parking lots and storage systems. This research sought to optimize the performance of a coastal parking lot integrated with tidal energy generation systems, which serve as an independent microgrid. An optimization problem is aimed at maximizing microgrid revenue and minimizing tidal energy loss along with practical microgrid constraints including island performance stability and equipment utilization constraints.